Legal and ethical issues in end of life care - Rathor, Mohammad Yousuf; Shahar, Mohammad Arif (2018)
End of life (EOL) care presents a number of legal and ethical challenges in all societies irrespective of their economic, cultural, or religious backgrounds. The issues range from attempts to prolong the lives of dying patients through highly advanced medical technologies, to efforts to terminate life prematurely through euthanasia and medically assisted suicide. Many physicians are unfamiliar with EOL care and tend to be more cautious than necessary. Frequently, many dying patients are subjected to CPR, intubated and put on ventilators. Then they feel helpless when there are no ventilators and ICU beds for patients who will benefit most from such care. Simply giving therapy which is of limited benefit and which may impinge on the rights and needs of others is not fair. The legal position is clear that competent adults have the right to refuse or discontinue medical interventions and that physician need not strive to preserve life at all costs. Similarly patients cannot demand a treatment that is not in their best interests. The physicians play an essential role in clarifying the goals of medical treatment at EOL, educating patients and families, helping them deliberate about a proposed treatment plan which is reasonably achievable and realistic. Therefore there is a need to disseminate relevant information to specific target groups and public in general about some key issues affecting care at the EOL. The objective of this article is to evaluate EOL preferences in clinical practice in Malaysia to help prioritize and enhance knowledge regarding advance care planning; DNR status, withdrawing and withholding treatment, etc. This will encourage optimal utilisation of hospital facilities and services thus reducing hospital operating costs due to prolonged unnecessary hospitalisation.